Preservation Strategies of the Cultural Heritage of the Historical Centers of Puebla, Havana and Quito - Ramírez-Rosete, Norma Leticia; González-González, María Jesús; Reyes-Granados, José Alejandro (Revista de Estudios Andaluces, 2020)
This research is based on a descriptive methodology regarding the main urban-architectural typological characteristics of the historic cities of Puebla, Havana and Quito, emphasizing current legislation and conservation policies for their protection. This is due to its complex and diversified political-administrative, cultural, tourist, etc. functions, which continue to maintain a certain homogeneity. However, some interventions jeopardize the conservation and preservation of their tangible and intangible cultural heritage. Therefore, this research is focused on analyzing and comparing regulatory plans and planning tools aimed at both the commercialization and the rehabilitation of the cultural identity of these Novo-Hispanic cities that currently play a relevant role as cultural heritage cities of humanity references Worldwide.